Serial verb constructions in Tai Long Shan - Soh, Jyr Minn (2019)
This dissertation provides a description and syntactic analysis of the Serial Verb Constructions (SVCs) in the Shan language, specifically the dialect of Tai Long Shan (TLS) that is spoken in the northern Shan State of Myanmar. Six chapters make up this paper, and the first chapter introduces the motivation for choosing to explore SVCs in Tai Long Shan, one of which is the lack of exploration of this language as compared to its sister languages. Other information about the Shan language and its speakers are also mentioned in this introductory chapter, and they include Shan’s genetic affiliation with other Tai Kadai language, the dialectal situation of the Shan language and the heavy history of its people. Following that is a typological overview of Tai Long Shan that would help readers gain some understanding about the phonology and constituency of the language. The last portion of this chapter examines the assumptions made about SVCs before arriving at a definition for SVCs in Shan. The second chapter details the methods used for the entire data collection process for this research. There are two kinds of data collected—elicited and natural. Elicited data include The Pear Story after watching the video, and describing the content of video clips made for the exploration of event representation in languages by Miriam van Staden, Gunter Senft, N. J. Enfield, and Jürgen Bohnemeyer. Natural data include the narration of a folktale called The Frog and Crow Story and a conversation between two participants. In the third chapter, the various types of SVCs are investigated and discussed in detail, and tests for verbhood are also done to demonstrate the differences between verbs and elements that seem verbal. There are both symmetrical and asymmetrical SVCs found in Shan. It is found that four types of SVCs: Sequential SVCs, Transfer SVCs, Purposive SVCs and Reciprocal SVCS. Under Sequential SVCs are subtypes Accomplishment SVCs, Resultative SVCs, Motion SVCs, and Adversative SVCs. Under Transfer SVCs is the subtype Manner SVCs. There are two different forms of SVCs and they are nuclear serializations and core serializations. Nuclear serializations involve the sharing of all arguments while argument-sharing in core serializations is partial. The fourth chapter of this study examines the syntactic structure of SVCs in Shan using the layered structure of the clause (LSC) framework in Role and Reference Grammar (RRG). An overview of the framework is given so that readers will have some working knowledge of the mechanisms that make up the framework. Following that, the different juncture-nexus types of SVCs in Shan are represented with the layered structure of the clause analysis. There are five juncture-nexus types in Shan and they are nuclear subordination, nuclear cosubordination, nuclear coordination, core cosubordination and core coordination. Lastly, this chapter ends by detailing the scope of negation for nuclear and core constructions. Grammaticalization is discussed in the fifth chapter, and it starts with an overview of this language phenomenon. The second part of this chapter discusses the grammaticalization paths of minor verbs ma44 ‘come’ and kwaa21 ‘go’ and how their directional senses extended into other contexts. The last part of this chapter includes the exploration of grammaticalized markers laj43 ‘get’ and pan214 ‘give’. Finally, the conclusion makes up the sixth and last chapter of this dissertation with suggestions for future research.